1999
DOI: 10.1074/jbc.274.40.28828
|View full text |Cite
|
Sign up to set email alerts
|

The Shedding of Membrane-anchored Heparin-binding Epidermal-like Growth Factor Is Regulated by the Raf/Mitogen-activated Protein Kinase Cascade and by Cell Adhesion and Spreading

Abstract: by PD98059. (iv) Whereas PMA induced HB-EGF TM HA/Myc shedding in attached cells, no shedding occurred when the cells were placed in suspension. Shedding was fully restored shortly after cells were allowed to spread on fibronectin, and the extent of PMA-induced shedding increased with the extent of cell spreading. PMA induced the same level of MAP kinase activation whether the cells were attached or in suspension suggesting that although MAP kinase activation might be necessary for shedding, it was not suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
159
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(182 citation statements)
references
References 60 publications
20
159
2
1
Order By: Relevance
“…Shedding of L-selectin is observed shortly after adhesion to endothelial cells (40) and may be essential for PMN migration (48). Furthermore, shedding of L-selectin depends on TACE (ADAM17) (40) and is regulated among other things by the MAPK p38 (41,42). Given the fact that p38 MAPK phosphorylation is inducible by SCFA via GPR43, as shown in this study (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Shedding of L-selectin is observed shortly after adhesion to endothelial cells (40) and may be essential for PMN migration (48). Furthermore, shedding of L-selectin depends on TACE (ADAM17) (40) and is regulated among other things by the MAPK p38 (41,42). Given the fact that p38 MAPK phosphorylation is inducible by SCFA via GPR43, as shown in this study (Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, MDC9, which shares sequence similarity with TACE in its cytoplasmic domain, is phosphorylated by protein kinase C␦ (51). In one study this phosphorylation was shown to regulate the induction of HB-EGF shedding by PMA (51), whereas other findings indicate that PMA may activate HB-EGF shedding through the Erk MAP kinase signaling pathway instead (33,35). We now show that growth factor or PMA stimulation leads to enhanced phosphorylation of TACE through activation of the Erk MAP kinase signaling pathway.…”
mentioning
confidence: 95%
“…In contrast, little is as yet known about natural inducers and signaling pathways that activate ectodomain shedding under physiological conditions. Recent studies (32)(33)(34)(35)(36) have uncovered the roles of mitogen-activated protein (MAP) kinase signaling pathways in the activation of ectodomain shedding. Thus, growth factors and activated tyrosine kinase receptors rapidly induce ectodomain shedding of TGF-␣ and other transmembrane proteins through induction of the Erk MAP kinase signaling pathway without the need for new protein synthesis (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The immune complexes were incubated with 40 l of protein G-Sepharose (50% vol͞vol slurry) for 1.5 hr at 4°C, washed four times with lysis buffer, and boiled in 2ϫ Laemmli's sample buffer. Proteins were resolved on 7% SDS͞PAGE and analyzed by Western blot by using monoclonal antiphosphotyrosine antibodies (16).…”
Section: Binding Of 125 I-vegf165 To Snrp1 and To Cells Binding In Smentioning
confidence: 99%